Effect of omalizumab on inflammatory markers in COVID-19: an exploratory analysis of the COVID-19 immunologic antiviral therapy with omalizumab (CIAO) trial - Prosty, Connor; Le, Michelle; Lu, Yang; Khoury, Lauren; Cormier, Maxime; Cheng, Mathew P.; Fowler, Robert; Murthy, Srinivas; Tsang, Jennifer LY; Lejtenyi, Duncan; Ben-Shoshan, Moshe; Rahme, Elham; et al. (Frontiers in Medicine, 2024)
Background The CIAO trial recently demonstrated a probable clinical benefit of omalizumab in the treatment of severe COVID-19; however, the mechanism underlying this benefit remains unclear. Therefore, we sought to longitudinally assess the impact of omalizumab on serum cytokines in CIAO trial patients to determine its mechanism of action. Methods Blood samples were collected on days 0, 2, 7, and 14 from patients recruited into the CIAO trial and who consented to this substudy. Blood samples were tested by a panel of 25 inflammatory cytokines, as well as for markers of mast cell activation. Levels of inflammatory biomarkers were compared over time between omalizumab- and placebo-treated patients by generalized linear mixed-effects model. Associations between biomarkers and clinical outcomes were investigated by mixed-effects logistic regression. Results Nineteen patients were recruited into this substudy; 10 were assigned to placebo and 9 to omalizumab. Monokine induced by gamma interferon was significantly positively associated with severe COVID-19 (Odds Ratio [OR] = 1.06, 95%CI = 1.00–1.11, p = 0.043). Further, omalizumab significantly reduced interleukin-15 (Coefficient = −0.95, p = 0.048) and macrophage inflammatory protein-1 (Coefficient = −1.31, p = 0.010) levels. However, neither was significant in analyses adjusting for multiple hypothesis testing. Conclusion Although limited by a small sample size, these results suggest that omalizumab’s potential benefit in COVID-19 may be mediated independently of modulation of the measured serum biomarkers. Further studies are needed to investigate omalizumab’s mechanism of action in COVID-19.